Active Flow Control using Dense Wireless Sensor and Actuator Networks - Robles, Ramiro (2018)
This paper describes the design of an active flow control (AFC) system for aeronautics applications based on dense wireless sensor and actuator networks (WSANs). The objective of this AFC system is to track gradients of pressure (or wall shear stress) across the surface of the fuselage of commercial aircraft. This collected information is used to activate a set of actuators that will attempt to reduce the skin drag effect produced by the separation between laminar and turbulent flows. This is expected to be translated into increased lift-off forces, higher vehicle speeds, longer ranges and reduced fuel consumption. The paper describes the architecture of the system in the context of the European research project DEWI (dependable embedded wireless infrastructure) using the concept of the DEWI Bubble and its three-tier architecture especially designed to ensure dependability and interoperability in industrial WSANs. A system-level simulator is also proposed to model each process of the AFC system and the aeronautics DEWI Bubble infrastructure, highlighting the interactions between the network simulation and the results of the computational fluid dynamics (CFD) simulation. The key element in the proposed solution is a polygonal patch of wired sensors and actuators. This patch is provided with a wireless link to a central coordinator or access point conveniently located in the aircraft to maximize coverage to a network of distributed patches. A trade-off between scalability, size of the patches, fluid speed/viscosity, sampling sensor and actuator rates in space and time, and the capacity/delay characteristic of the wireless inter-patch and the wireline intra-patch communication technologies is also here discussed. The hybrid wireless/wired sensor and actuator network achieves great flexibility, scalability, manageability, troubleshooting, and modularity as compared to a solution exclusively based on wireline or wireless components. The final details of the prototype and results in a wind tunnel test-bed are here described, demonstrating the validity of the concept and the use of wireless technologies for aeronautical applications (flexible architecture and innovative services). Future issues regarding security, safety and trustiness of the AFC system are also briefly introduced in the context of the spin-off European project SCOTT (secure connected trusted things).